Study on Formation Mechanism and Demonstration Method of Equipment Acquisition Price - Li Yanjie, Lin Jia, Wang Xianglin (Hangkong bingqi, 2024)
With the deepening of equipment price management reform, the equipment acquisition price has increasingly become the core of comprehensive price control. In response to fundamental issues such as unclear understanding of the formation mechanism of equipment acquisition price and unreasonable selection of argumentation me-thods in military and enterprise at the current stage, based on deep analysis in concepts of the equipment acquisition price, this paper concludes its basic characteristics and evaluation criteria. Based on the principles of system engineering and the equipment life cycle cost, it studies the formation mechanism of the equipment acquisition price, and analyzes the influencing factors of the equipment acquisition price, standardizes the demonstrating process and work items for the equipment acquisition price. On the basis of the cost attribute oriented argumentation methods, such as traditional engineering methods, parameter methods, analogy methods, this paper puts forward the economic affordability analysis method, war cost analysis method, and cost-effectiveness evaluation method for the demand attributes and benefit attributes. It sets up the method system of the equipment acquisition price to provide effective instructions in practice of the equipment acquisition price demonstration, and to increase the scientificity and rationality of equipment acquisition price demonstration results.